Neuroprotective effects of Kukoamine A against cerebral ischemia via antioxidant and inactivation of apoptosis pathway. (July 2017) - Liu, Jia; Jiang, Xiaowen; Zhang, Qiao; Lin, Sen; Zhu, Jun; Zhang, Yajun; Du, Jiabao; Hu, Xiaolong; Meng, Weihong; Zhao, Qingchun
Abstract: Kukoamine A (KuA) is a bioactive compound, which is known for a hypotensive effect. Recent studies have shown that KuA has anti-oxidative effect and anti-apoptosis stress in vitro . However, its neuroprotective effect in rats with cerebral ischemia is still unclear. In the study, we investigated whether KuA could attenuate cerebral ischemia induced by permanent middle cerebral artery occlusion (pMCAO) in rats. Results revealed that KuA could significantly reduce infarct volume both pre-treatment and post-treatment, and increase corresponding Garcia neurological scores. Acute KuA postconditioning not only significantly reduced cerebral infarct volume, brain water content and improved neurological deficit scores, but also decreased the number of TUNEL-positive cells. Moreover, it markedly increased the activities of Cu/Zn-SOD and Mn-SOD, reduced levels of MDA and H2 O2. Increased expressions of caspase-3, cytochrome c and the ratio of Bax/Bcl-2 were significantly alleviated with KuA treatment. These findings demonstrated that KuA was able to protect the brain against injury induced by pMCAO via mitochondria mediated apoptosis signaling pathway. Highlights: KuA could reduce the infarct volume both in pre-occlusion and post-occlusion. KuA could attenuate brain swelling and the number of apoptotic cells in the ischemic brain. The potential mechanisms may be involved in modulating oxidative status and inactivation mitochondrial apoptosis pathway.